Actinic keratosis with atypical basal cells (AK I) is the most common lesion associated with invasive squamous cell carcinoma of the skin. (26th November 2014) - Fernández‐Figueras, M.T.; Carrato, C.; Sáenz, X.; Puig, L.; Musulen, E.; Ferrándiz, C.; Ariza, A.
Abstract: Background: Progression from actinic keratosis (AK) to invasive squamous cell carcinoma (iSCC) of the skin is thought to occur after the development of full thickness epidermal neoplasia, as in the classic pathway of cervical cancer. Nevertheless, cutaneous iSCC may also directly arise from a proliferation of atypical basaloid cells limited mostly to the epidermal basal layer (AK I), akin to what happens in the 'differentiated pathway' of iSCC of the vulva, oral cavity and other locations. Objective: To evaluate the prevalence of classic and differentiated pathways in the development of cutaneous iSCC. Methods: The epidermis adjacent to and overlying iSCC, assumed to be representative of pre‐existing lesions, was histologically studied in 196 skin biopsy specimens showing iSCC. Results: AK I, AK II and AK III lesions overlying iSCC were present in 63.8%, 17.9% and 18.4% of cases respectively. The corresponding percentages in the epidermis adjacent to iSCC were 77.9%, 6.6% and 8.3% respectively (stage could not be assessed in 8.1% of cases). Focal epidermal ulceration overlying iSCC was seen in 32% of AK I, 28.6% of AK II and 33.3% of AK III instances. Adnexal involvement by atypical keratinocytes (proliferative AK) was present more frequently in cases with overlying AK I (39/125, 31.2%) than with AK II (8/35, 22.9%) and AKII I (5/36, 13.9%). Conclusion: Direct invasion from proliferating basaloid atypical keratinocytes limited to the epidermal basal layer (AK I), known as the differentiated pathway, was the most common form of progression to cutaneous iSCC in our series. On the other hand, stepwise progression from AK I to AK II and AK III (classic pathway) was seen to be operative in a substantial proportion of iSCC cases. All AK lesions, irrespective of intraepidermal neoplasia thickness, are therefore potentially invasive and tumour advance along adnexal structures might facilitate iSCC development from AK I lesions.